Controlled, cross‐sectional MRI evaluation of joint status in severe haemophilia A patients treated with prophylaxis vs. on demand. (2nd December 2014) - Oldenburg, J.; Zimmermann, R.; Katsarou, O.; Theodossiades, G.; Zanon, E.; Niemann, B.; Kellermann, E.; Lundin, B.; ,
Summary: In patients with haemophilia A, factor VIII (FVIII) prophylaxis reduces bleeding frequency and joint damage compared with on‐demand therapy. To assess the effect of prophylaxis initiation age, magnetic resonance imaging (MRI) was used to evaluate bone and cartilage damage in patients with severe haemophilia A. In this cross‐sectional, multinational investigation, patients aged 12–35 years were assigned to 1 of 5 groups: primary prophylaxis started at age <2 years (group 1); secondary prophylaxis started at age 2 to <6 years (group 2), 6 to <12 years (group 3), or 12−18 years (group 4); or on‐demand treatment (group 5). Joint status at ankles and knees was assessed using Compatible Additive MRI scoring (maximum and mean ankle; maximum and mean of all 4 joints) and Gilbert scores in the per‐protocol population ( n = 118). All prophylaxis groups had better MRI joint scores than the on‐demand group. MRI scores generally increased with current patient age and later start of prophylaxis. Ankles were the most affected joints. In group 1 patients currently aged 27−35 years, the median of maximum ankle scores was 0.0; corresponding values in groups 4 and 5 were 17.0 and 18.0, respectively [medians of mean index joint scores: 0.0 (group 1), 8.1 (group 2) and 13.8 (group 4)]. Gilbert scores revealed outcomes less pronounced than MRI scores. MRI scores identified pathologic joint status with high sensitivity. Prophylaxis groups had lower annualized joint bleeds and MRI scores vs. the on‐demand group. Primary prophylaxis demonstrated protective effects against joint deterioration compared with secondary prophylaxis.